Longitudinal MRI Volumetric Evaluation in Patients with Familial Mesial Temporal Lobe Epilepsy - Conz, Livia; Morita, Marcia E.; Coan, Ana Carolina; Kobayashi, Eliane; Yasuda, Clarissa L.; Pereira, Amanda R.; Lopes-Cendes, Iscia; Cendes, Fernando (Frontiers in Neurology, 2011)
Introduction: Studies have shown progressive cerebral damage in patients with refractory mesial temporal lobe epilepsy (MTLE). However, this has not been demonstrated in benign forms of MTLE such as familial MTLE (FMTLE). Purpose: To evaluate progression of hippocampal atrophy (HA) in patients with sporadic (SMTLE) and FMTLE by longitudinal MRIs acquired with at least seven months of interval. Method: We included 35 patients with FMTLE (25 classified as benign and 10 refractory) and 33 with SMTLE (4 benign and 29 refractory). All MRIs were analyzed by an investigator blind for clinical data. Hippocampal analyses were performed manually in coronal 3mm thick T1 inversion recovery, using the software Scion Image®. Volumes were compared to those from a control group, and HA was determined for volumes below two standard deviations from the mean of controls. Results: The mean interval between the first (MRI1) and second MRI (MRI2) was 90 months for FMTLE and 45 months for SMTLE group. FMTLE group: volumetry demonstrated HA in 20 patients in MRI1 and in 23 patients in MRI2. There was significant progression of HA in FMTLE patients between MRIs in both benign and refractory FMTLE patients (benign FMTLE: right hippocampus, p=0.001 and left hippocampus, p<0.001; refractory FMTLE: right hippocampus, p=0.022 and left hippocampus, p<0.010). SMTLE group: volumetry demonstrated HA in 27 patients in MRI1 and in 29 patients in MRI2. In the group analysis, there was a significant reduction of the right (p<0.0001) and left (p<0.0001) hippocampal volumes during the follow-up period. Although the mean time between the MRIs in the FMTLE group was twice the time of the SMTLE group, the progression of volume loss was similar in both groups, indicating a slower progression in the FMTLE patients. Conclusion: FMTLE patients have progressive hippocampal volume reduction independently of seizure frequency although the progression of HA seems to be slower than in SMTLE.